Reading and writing from literature - Schwiebert, John E., 1955- (Houghton Mifflin, 1997)
This book is divided into five parts: Writing and Reading: Interrelated Activities; Writing Essays About Literature; Creating a Writing Portfolio; An Introduction to the Four Major Genres; and A Thematic Anthology of Reading.